Environmental Management Strategy to Control Air Germs in Tjitrowardojo District Hospital - Juni Praptiwi; Setyo Sri Rahardjo; Sunarto Sunarto (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: The presence of air germs in the hospital patient rooms is potentially to cause health problems for patients. This study aimed to identify andanalyze environmental factors associated with air germs, and formulate environmental management strategi to control air germs in the patient rooms. Methods: This study was an observational analytic survey, used a mixed method and a cross sectional design. Data collection was conducted through laboratory tests and interviews. Data was analysed by pearson correllation test to analyze environmental factors associated with air germs. The appropriate environmental management strategies was determined through SWOT analysis (Strength, Weakness, Opportunities, Threats). Results and Discussion: Several factors related to air germs were temperature (p = 0.032), lighting (p = 0.01) and the staff knowledge (p = 0.001). Humidity was not significantly related to air germs (p = 0.178), The results of SWOT analysis indicated that aggressive strategies (Strengths and Opportunities) were arranging internal hospital policies regarding to air quality management based on the Ministry of Health, utilizing educational qualifications and knowledge of room staff to support policy implementation, improving the performance of outsourcing personnel in cleaning services and maintaining hospitals infrastructure, increasing Inhouse Training activities. Conclusion: Environmental factors play an important role in the presence of air germs in the patient rooms so appropriate environmental management strategies are needed to control the presence of air germs.